Digital economies SMEs and e-readiness - Mutula, Stephen M. (Business Science Reference, 2010)
"This book provides valuable insights into the current state of the digital economy and the ability of SMEs to leverage Information and Communication Technologies (ICTs) so that they may overcome their traditional laggard position in the global business market"--Provided by publisher.